2020
DOI: 10.1016/j.encep.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Prisons confinées : quelles conséquences pour les soins psychiatriques et la santé mentale des personnes détenues en France ?

Abstract: Article de recherchePrisons confinées : quelles conséquences pour les soins psychiatriques et la santé mentale des personnes détenues en France ?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 45 publications
(56 reference statements)
0
19
0
5
Order By: Relevance
“…The majority of papers were opinion pieces, with the exception of 10 case studies, [30][31][32][33][34][35][36][37][38][39] seven guidelines, 13-16 40-42 six literature reviews, [43][44][45][46][47][48] five qualitative studies, [49][50][51][52][53] three cross-sectional studies, [54][55][56] three briefings, [57][58][59] three case studies 37 39 60 and one study protocol. 61 All assessed studies were found to be of poor quality (see online supplemental appendix 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of papers were opinion pieces, with the exception of 10 case studies, [30][31][32][33][34][35][36][37][38][39] seven guidelines, 13-16 40-42 six literature reviews, [43][44][45][46][47][48] five qualitative studies, [49][50][51][52][53] three cross-sectional studies, [54][55][56] three briefings, [57][58][59] three case studies 37 39 60 and one study protocol. 61 All assessed studies were found to be of poor quality (see online supplemental appendix 3).…”
Section: Resultsmentioning
confidence: 99%
“…35 43 47 70 73-78 Many were concerned that isolation may lead to exacerbations of mental health conditions, anger, depression, psychosis, self-harm and suicide. 39 46 56 66 72 74-76 [79][80][81][82][83][84] There were also concerns that isolation in JCFs will affect young offenders' neurological development. 63 74 85 In this context, it is important to clarify the difference between isolation and solitary confinement.…”
Section: Fear Of Covid-19mentioning
confidence: 99%
“…Therefore, mental health should be at the forefront of considerations when implementing infection control measures in prisons to mitigate adverse consequences for PIP. [91][92][93] Finally, a key consideration that is not addressed in any of the included papers are the consequences of how health services in prison are commissioned and their level of integration with community health systems. Separate systems are more prone to breakdowns and delays in follow-up care, which will be necessary to ensure treatment completion and epidemiological surveillance.…”
Section: Research Gapsmentioning
confidence: 99%
“…Die psychiatrische Akutversorgung müsse sich auf die Behandlung schwer psychisch erkrankter SARS-CoV-2-Infizierter vorbereiten [ 12 ], als Reaktion auf die täglich wechselnden Hygienemaßnahmen bestünde die Notwendigkeit, „fast täglich die Psychiatrie neu“ zu „erfinden“ [ 31 ], ähnlich wie in der Psychiatrischen Universitätsklinik der Charité im St. Hedwig-Krankenhaus umgesetzt (PUK der Charité im SHK; [ 17 ]). Faktisch bedeutete die COVID-19-Pandemie-bedingte Umstrukturierung der psychiatrischen Akutstationen, dass mehr schwer psychisch Erkrankte auf weniger stationäre Behandlungsplätze trafen und daher ambulant mitbehandelt werden mussten.…”
unclassified